OP0208 EFFECT OF SERUM URATE LOWERING WITH ALLOPURINOL ON BLOOD PRESSURE IN YOUNG ADULTS. (June 2019) - Gaffo, Angelo; Calhoun, David; Rahn, Elizabeth; Oparil, Suzanne; Muntner, Paul; Peng, LI; Redden, David; Dudenbostel, Tanja; Foster, Jeff; Biggers, Stephanie; Feig, Daniel; Saag, Kenneth
Abstract : Background: The association between serum urate and hypertension continues to be controversial. Animal models and studies in adolescents provided strong support of urate- lowering therapy (ULT) efficacy to improve early hypertension (1), while one recent randomized-controlled study in adults failed to find benefit (2). Objectives: To test the hypothesis that serum urate reduction with allopurinol would lead to blood pressure reductions in young adults with pre-hypertension. Methods: Single center, double-blinded, crossover trial in which participants were randomly assigned to allopurinol (300 daily mg) or placebo for a period of one month each. Adults ages 18-40, with baseline systolic blood pressure (SBP) ≥ 120 and < 160 mm Hg or diastolic blood pressure ≥ 80 and < 100 mm Hg, and serum urate ≥ 5.0 mg/dL (>297.4 µmol/L) or ≥ 4.0 mg/dL (237.9 µmol/L) (men or women, respectively) were enrolled. Main exclusion criteria included chronic kidney disease, gout, or use of ULTs. The primary outcome was change from baseline in SBP assessed by 24 hour ambulatory blood pressure monitoring. Safety assessments were also conducted. Results: 99 participants were randomized, and 82 completed study participation (Table 1). Serum urate decreased by -1.33 ± 1.21 mg/dL (-79.1 ± 72.0 µmol/L) during the allopurinol period (p<0.001) and by a non-significant -0.04 ± 0.75 mg/dL (2.4 ± 44.6 µmol/L) while taking placebo. SBP changed by -0.71 ± 8.21 mmHg during the period assigned to allopurinol versus -0.16 ± 7.33 mmHg during the period assigned to placebo. The difference between these changes in SBP was not significant (p=0.52) (Table 2). Changes in diastolic blood pressure and mean ambulatory blood pressure also were not significantly different during allopurinol and placebo exposure periods. In post hoc analyses, there was a trend towards significant blood pressure decreases in the small participant subgroup with serum urate of > 6.5 mg/dL (> 386.7 µmol/L) at baseline visit. No allopurinol hypersensitivity events or other serious adverse events were observed. Conclusion: In the intention-to-treat analysis, urate -lowering therapy with allopurinol in young adults did not lead to reductions in blood pressure when compared with placebo. Blood pressure reductions with allopurinol may be limited only to participants with higher baseline serum urate levels. References: [1] Feig DI, Soletsky B, Johnson RJ. JAMA. 2008;300:924-32. [2] McMullan CJ, Borgi L, Fisher N, et al. Clin J Am Soc Nephrol. 2017;12:807-16. Disclosure of Interests: Angelo Gaffo: None declared, David Calhoun: None declared, Elizabeth Rahn: None declared, Suzanne Oparil: None declared, Paul Muntner Grant/research support from: Dr. Muntner declares research grant from Amgen, Peng Li: None declared, David Redden: None declared, Tanja Dudenbostel: None declared, Jeff Foster: None declared, Stephanie Biggers: None declared, Daniel Feig: None declared, Kenneth Saag Grant/research support from: Amgen, Ironwood/AstraZeneca, Horizon, SOBI, Takeda, Consultant for: Abbvie, Amgen, Ironwood/AstraZeneca, Bayer, Gilead, Horizon, Kowa, Radius, Roche/Genentech, SOBI, Takeda, Teijin